A Comparative Study on the Performance of Metroxylon Sagu and Metroxylon Rumphil Grown on Gleyed Mineral Soil and Organic Soil - Lim, Kelvin Eng Tian (1991)
Sago palm is currently one of the major starch resources in Malaysia, as indicated by the M$14 million average annual export value obtained in the past few years. The two main types of sago palms found in Sarawak are the smooth sheathed Metroxylon sagu and spiny sheathed Metroxylon rumphii. These are grown all over Sarawak on different soil types ranging from mineral soil, shallow peat and deep peat. To date, no information is available on the performance of these two varieties grown on these soil types. This study was conducted to determine the effect of soil types on the growth, physical characteristics of the palms, the starch quality, and yield of the resultant starch extracted from these palms. The longitudinal and radial starch distribution of the palm, the different methods of estimating starch yields and the leaf nutrient variation of the sago palm were also evaluated.Results from this study indicated that sago palm performed better on mineral soil than on the marginal peat soil with starch yield ranging from 182 to 260 kg / trunk for Metroxylon sagu in mineral soil compared to 128 to 188 kg / trunk in deep peat. In terms of starch yields against palm maturity, total starch yield was found to increase with palm age up to the 'Angau Muda' (flowering) stage after which the total starch content decreased sharply. The physico-chemical characteristics of the sago starch from both varieties and different stages of maturity did not differ significantly. The longitudinal and radial distribution of the starch in trunk of the palm was uneven. The upper portion of the trunk and the outer segment of the pith had lower starch contents. The starch yield per trunk of sago can be estimated by measuring the trunk length and girth at breast height. Studies showed that estimating of starch yield based on volume basis is easier and more accurate. The study on the variation leaf nutrient content of sago palm recommended frond 9 be sampled for the assessment of the nutrient status of the palm.